Differences in Robbery Prevention Strategies Across Retail Business Types. Issue 2 (February 2019) - Davis, Jonathan; Casteel, Carri; Nocera, Maryalice; Summers, Robert; Peek-Asa, Corinne
Abstract : Objective: To compare implementation of robbery prevention strategies between gas station/convenience stores with liquor stores/grocery stores/pharmacies, restaurants/bars, and other retail businesses. Methods: One hundred forty-nine retail businesses were evaluated by police personnel across four police departments for adherence to robbery prevention strategies. Assessment of these strategies occurred between November 2012 and October 2014. Implementation of these strategies were compared across business types using logistic regression. Results: Liquor/grocery stores/pharmacies and restaurants/bars were less likely to have a high site assessment score for robbery prevention elements when compared with gas station/convenience stores. Conclusions: Non-gas station/convenience stores require stronger consideration when developing robbery prevention programs and policies to assure appropriate implementation of robbery prevention strategies.